Amorphous carbon coatings for total knee arthroplasty – A knee simulator evaluation - Neusser, Kevin; Marian, Max; Bartz, Marcel; Wartzack, Sandro; Rothammer, Benedict (64. Tribologie-Fachtagung. Reibung, Schmierung und Verschleiß. Forschung und praktische Anwendungen., 2023)
The purpose of endoprosthetic joint replacement is to regain the functionality and allow patients to live a more mobile and pain-free life. Aseptic loosening of total knee arthroplasty (TKA) is a major cause of premature failure, with wear particles removed from the implant materials being largely responsible. Therefore, great efforts are being made to reduce the wear of polymer inlays by surface modifications. This study concentrates on the evaluation of the effectiveness of wear-reducing amorphous carbon coating systems on hard-on-soft pairings (metal-on-polymer). The biotribological behavior of the uncoated and coated TKA is investigated in a knee simulator according to ISO 14243. The articulation is lubricated with diluted bovine calf serum (BCS) at 37 °C mimicking in vivo boundary conditions and motion parameters. The wear is quantified by gravimetry after a total of 3.5 million cycles and the gravimetric wear of the polymeric tibial inlays are calculated in intervals of 500,000 cycles. This testing reveals the applicability of amorphous carbon (also known as diamond-like carbon (DLC)) coatings to the considered materials used for biomedical applications. The results represent an important milestone in demonstrating the potential of DLC coated contact partners for wear reduction in human joints, thus enabling more focused research and understanding in the development of biotribologically effective coating systems. <